Mitsunobu Reaction with 4-(Diphenylphosphino)benzoic Acid: A Separation-Friendly Bifunctional Reagent that Serves as Both a Reductant and a Pronucleophile - Muramoto, Natsuko; Yoshino, Kazuki; Misaki, Tomonori; Sugimura, Takashi (Synthesis, 2013)
4-(Diphenylphosphino)benzoic acid was used for the Mitsunobu reaction as a bifunctional reagent that served as both a reductant and a pronucleophile. When combined with di-2-methoxyethyl azodicarboxylate, inversion of a secondary alcohol stereospecifically occurred to give an ester carrying a phosphine oxide group. The reaction mixture was directly hydrolyzed to give an inverted secondary alcohol in sufficient stereo and chemical purities by the presently developed chromatography-free process in conjunction with basic extraction, drying, and concentration.
Keywords: alcohols; substitution; Mitsunobu reaction; phosphorus